CircRNA circ_0055724 Inhibits Trophoblastic Cell Line HTR-8/SVneo's Invasive and Migratory Abilities via the miR-136/N-Cadherin Axis. (22nd June 2022) - Xu, Xiaohong; Teng, Hong
Abstract : Preeclampsia (PE) is one of the major causes of morbidity and mortality in pregnancy. According to recent research, circular RNAs (circRNA) may act as sponges for microRNAs (miRNAs) and modulate gene expression. Low expression of hsa_circ_0055724 (circ_0055724) in PE tissues was recently reported in literatures. However, its mechanism and function have not been reported. Therefore, we were committed to investigating the role and mechanism of circ_0055724 in PE. Our study first verified the low expression of circ_0055724 in PE tissues. Overexpression or knockdown of circ_0055724 enhances/weakens the trophoblast cell survival, migration, and invasion. Furthermore, CircInteractome predicted the binding sites of circ_0055724 and miR-136, while Starbase predicted miR-136 targeted N-cadherin. Luciferase reporter gene assay confirmed that circ_0055724 directly interacts with miR-136 and miR-136 directly interacts with N-cadherin. More results indicated that high expression of miR-136 and low expression of N-cadherin appeared in PE. Increased expression of circ_0055724 resulted in decreased miR-136 but increased N-cadherin expression. Hence, circ_0055724 and N-cadherin were positively correlated, while circ_0055724 and miR-136 had a negative correlation. In terms of mechanism, circ_0055724 may induce the expression of N-cadherin and regulate the proliferation, migration, and invasion of trophoblast cells through decreasing miR-136, which can be a promising biomarker for early diagnosis and prognosis of patients with PE.